STUDI EVALUASI PEMANFAATAN PEDESTRIAN SEBAGAI FASILITAS PEJALAN KAKI PADA RUAS JALAN SOEKARNO HATTA KOTA BUKITTINGGI - Eric Muharnis; Ishak Ishak; Yorizal Putra (Ensiklopedia Research and Community Service Review, 2023)
Abstract: The development of pedestrian paths for the convenience of users is one of the considerations in the development and improvement of infrastructure quality. The purpose of this study is to analyze and evaluate pedestrian facilities in the Soekarno Hatta Street area, to find out whether the pedestrian path has functioned optimally and whether it meets the planning standards used, and to determine the perceptions and preferences of pedestrian path users. The data collection method used in this research is through random sampling technique, documentation technique, questionnaire or questionnaire, interview technique (interview), while the data processing tool is Microsoft Excel. The results of the research from a physical point of view regarding the location of pedestrian paths with an effective width of ± 1.5 meters already have pedestrian paths that are in accordance with the minimum standards of pedestrian paths in urban areas. For the aspect of user satisfaction on the condition of the pedestrian path, the percentage result is 52.2%. Based on the results of the study, it can be concluded that for the aspect of user satisfaction on the condition of the pedestrian path, it belongs to the Quite Comfortable (CN) criteria, for perceptions and preferences of the main comfort factor according to respondents, namely the shade must be improved, while for the inconvenience factor, namely too hot and parking. illegal activities, as well as the lack of road signs and infrastructure. Factors to increase comfort are the need to increase lighting facilities, benches, trash cans, and increase shade trees/canopies, analysis of perceptions and preferences about the function of pedestrian paths that choose the function of pedestrian paths as pedestrian paths, city beauty spaces and vehicle waiting rooms as the main priority, namely respondents stated consistent. The research analysis for validity using the SPSS application program from 12 question items regarding the condition of the pedestrian path was declared valid and for reliability it was declared reliable.Keywords: Comfort, Pedestrians, Pedestrian Paths.